Data sensing and computation technologies for amimal welfare - Ruhil, A P; Mohanty, T K; Lathwal, S S (Indian Farming, 2019)
Dairy farm management is becoming a knowledge intensive activity with global presure to increase the milk productivity of animal with minimum inputs and maximum animal comfort. Knowledge on various aspects of livestock management is required to make it a profitable venture. The profitability depends upon quality of decision making which in turn depends upon the quality of information as well as the speed with which the required information is made accessible to the farm manager. The technological developments in field of artificial intelligence, block chain, cloud technologies and data science (ABCD technologies) are going to transform the practice of traditional dairy farming into smart dairy farming.